Modern opportunities for assessing the left ventricle remodeling - V. V. Syvolap; A. O. Bohun (Zaporožskij Medicinskij Žurnal)
Aim: To compare the results of distributing left ventricular (LV) remodeling patterns according to two classifications and identify their advantages and disadvantages.